COVID-19 Strengthens the Solidarity and Association of Southeast Asian Nations - Japan Cooperation - Mohd Huda, Mohd Ikbal; Adilah Masrol, Siti Noor (WILAYAH: The International Journal of East Asian Studies, 2021)
This article examines the initiatives of The Association of Southeast Asian Nations (ASEAN) and Japan through the cooperation of Government to Government (G2G) and the Special ASEAN Summit to combat the pandemic collectively. The initial cooperation through the coordinated â€œIntegrated Recovery Planâ€ has been very significant for the future of ASEAN and the resilience of a post-COVID-19 world by way of maintaining market stability in order to avoid the potential risk of economic recessions and public health emergencies. This synergism is seen as one of the best mechanisms to help ASEAN in ensuring socio-economic activities are restored and the welfare of about 600 million people is addressed. This research found that ASEAN Plus Three (APT) cooperation should formulate a Regional Recovery Plan and emphasize that the continuity of the supply chain should be maintained to ensure a smooth flow of food and medical supplies. Secondly, APT cooperation needs to be committed to the continuation of opening up markets, maintaining normal trade, services and investment flow in order to continue strengthening regional economic resilience. Thirdly, APT needs to formulate a plan that focuses not only on financial aspects (post-COVID-19 economic recovery) but also on social security networks, food security and education.